Sleeping Habits of Teenagers in a Multi-Cultural Community: A Case Study - Chrissutianto, Nicolas; Gladstone, Ranjith Kingston (11th International Scholars Conference, 2018)
Sleep is an essential phase of every living being’s everyday life cycle. However, activities engaged in this modern world by the teenagers cause lack of sleep, resulting in negative impact. In addition, both restoration theory by Oswald and Hibernation theory of Webb explain the results of lack of sleep to be causing daydreams, restlessness in the body, having difficulty with memory, etc. Studies done in this area highlights the cause and challenges of teenagers’ sleep deprivation, but there are no direct studies done in relation with multicultural community. Therefore, this qualitative research identified the factors of sleeping deprivation for teenagers in a multicultural community using case study design. There were 12 participants as purposive sampling from the 70 countries representatives who are residing in an International Higher Education Institution. Data were collected through interviews, focus group, and observation. Upon coding the data, categories, themes were developed. Findings revealed that the major causes are: activities for the self (video games, watching movie, social media), mental activities (having too much napping), and physical activities (house chores). Recommendations are presented to both teenagers and the teachers who may deal with them in the classroom.